2005
DOI: 10.1002/jmv.20310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different serological techniques for primary diagnosis and monitoring of nasopharyngeal carcinoma in two age groups from Tunisia

Abstract: Nasopharyngeal carcinoma (NPC) in Tunisia is characterized by its bimodal age distribution involving juvenile patients of 10-24 years and adult patients of 40-60 years. Three serological techniques were compared for primary diagnosis (N = 117) and post-treatment monitoring (N = 21) of NPC patients separated in two age groups. Immunofluorescence assay (IFA) was used as the "gold standard" for detection of IgG and IgA antibodies reactive with Epstein-Barr virus (EBV) early (EA) and viral capsid (VCA) antigens. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
65
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 35 publications
9
65
1
2
Order By: Relevance
“…Lytic-cycle products are rarely expressed in the NPC tumor cells but may originate from viral replication in differentiating NPC cells (51). The assessment of anti-EBNA1, anti-EA, and anti-VCA antibodies requires separate assays, each contributing to NPC diagnosis (23). Individual NPC patients may respond quite differently to EBV lytic-cycle proteins, but the small capsid protein VCA-p18, encoded by the BFRF3 reading frame, is a highly prevalent target for antibody responses, including IgG and IgA (3,9,13,23,35,44).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lytic-cycle products are rarely expressed in the NPC tumor cells but may originate from viral replication in differentiating NPC cells (51). The assessment of anti-EBNA1, anti-EA, and anti-VCA antibodies requires separate assays, each contributing to NPC diagnosis (23). Individual NPC patients may respond quite differently to EBV lytic-cycle proteins, but the small capsid protein VCA-p18, encoded by the BFRF3 reading frame, is a highly prevalent target for antibody responses, including IgG and IgA (3,9,13,23,35,44).…”
mentioning
confidence: 99%
“…The assessment of anti-EBNA1, anti-EA, and anti-VCA antibodies requires separate assays, each contributing to NPC diagnosis (23). Individual NPC patients may respond quite differently to EBV lytic-cycle proteins, but the small capsid protein VCA-p18, encoded by the BFRF3 reading frame, is a highly prevalent target for antibody responses, including IgG and IgA (3,9,13,23,35,44). However, high titers of IgG against EA/VCA are not specific for NPC and can be observed in other EBV-linked diseases as well (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combined detection of anti-NA1, anti-early antigen (EA), anti-viral capsid antigen and anti-replication and transcription activator increases the sensitivity and has been considered as a useful serological method for NPC screening and diagnosis (16)(17)(18)(19)(20). Salivary IgA antibody titers were previously reported to be increased in response to EA, gp340 or NA1-p107 in healthy individuals compared with patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Specific antibody responses to EBV proteins have become a powerful tool to detect reactivation of this virus in human body. Previous studies reported various serological biomarkers as prognostic factors with inconsistent results (Karray et al, 2005;Liu et el., 2004;Neel and Taylor, 1990;Yip et al, 1994;de Vathaire et al, 1988). Fan et al (2004) reported the use of IgA early antigen (EA) serology to predict post treatment outcome.…”
Section: Discussionmentioning
confidence: 99%